Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17051686
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Mumps Virus Infection: Epidemiology, Pathogenesis, and Vaccine

Abstract: Mumps is an important childhood infectious disease caused by mumps virus (MuV). We reviewed the epidemiology, pathogenesis, and vaccine development of mumps. Previous studies were identified using the key words “mumps” and “epidemiology”, “pathogenesis” or “vaccine” in MEDLINE, PubMed, Embase, Web of Science, and Google Scholar. We excluded the articles that were not published in the English language, manuscripts without abstracts, and opinion articles from the review. The number of cases caused by MuV decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 111 publications
(187 reference statements)
1
44
0
4
Order By: Relevance
“…Several reviews, both observational and systematic have demonstrated the clinical benefit of a mumps vaccine ( 107 , 108 ), the pathogenesis and genomic diversity of the MuV ( 10 , 107 , 108 ) and the epidemiology surrounding the outbreak ( 1 , 10 , 82 ). It is not clear why these mumps outbreaks occur, although it has been alluded to be due to a number of interrelated factors, such as sub-optimal vaccine uptake ( 1 , 109 , 110 ), primary or secondary vaccine failure or failure of the mumps vaccine to protect individuals from infection (vaccine efficacy) ( 107 ) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews, both observational and systematic have demonstrated the clinical benefit of a mumps vaccine ( 107 , 108 ), the pathogenesis and genomic diversity of the MuV ( 10 , 107 , 108 ) and the epidemiology surrounding the outbreak ( 1 , 10 , 82 ). It is not clear why these mumps outbreaks occur, although it has been alluded to be due to a number of interrelated factors, such as sub-optimal vaccine uptake ( 1 , 109 , 110 ), primary or secondary vaccine failure or failure of the mumps vaccine to protect individuals from infection (vaccine efficacy) ( 107 ) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The style of communication also has a significant impact on parents' perception of vaccinations [2]. It seems, therefore, that it is necessary to conduct longterm educational activities about vaccinations in order to increase the number of vaccinated children and thus obtain the aforementioned herd immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Children are the most prone to contract these three different viruses. The long-term complications vary from mild to dangerous or even death [1][2][3]. The World Health Organisation (WHO) reported that 82,596 people suffered from measles in the European region in 2018 and 72 died [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations